DAYA SAING EKONOMI INDONESIA : COOPERATION MULTILATERAL DAN REGIONAL - Riani, Novi; Harris, Allan; Maruf, Chasan (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2024)
The recent dynamics of global economic development provide clues about the importance of increasing competitiveness. As a member of the international community, Indonesia always collaborates with other countries. The research method used in this research is qualitative research. Regional and multilateral cooperation, especially through ASEAN, the UN and the WTO, have a major influence on Indonesia's economic policies and also play a role in increasing the country's economic competitiveness. By actively participating in international forums, Indonesia can influence the formation of trade rules and support them. Sustainable building and enhancing reputation as a reliable trading partner. The application of information technology and digital transformation through regional and multilateral cooperation plays an important role in increasing Indonesia's economic competitiveness and responding to the challenges of the industrial revolution 4.0 in the global market. This collaboration opens up opportunities for knowledge exchange, access to global resources, and strengthens the innovation ecosystem that maintains sustainable economic growth. Although there are still several obstacles that need to be resolved, Indonesia's participation in this collaboration has created a strong foundation for maximizing the potential of digital transformation to realize the vision of a modern and inclusive economy